Implications of salience theory: Does the independence axiom always hold under uncertainty? - Christoph Ostermair (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2018)
So far, "salience theory of choice under risk" has been mainly applied to situations of risk rather than to those of uncertainty. In this paper, we show that salience theory provides the prediction that Allais paradoxes should never occur in the context of uncertainty. A finding which contra-dicts the scarce evidence existing up to now, and which indicates that further research on the topic is necessary.
Keywords: D81; 330; Models of decision-making under risk and uncertainty; Allais paradox; Independence axiom; Salience theory